Expression profile, subcellular localization and signaling pathway analysis of fish-specific TLR25 in Nile tilapia (Oreochromis niloticus). Issue 104 (September 2020) - Lee, Po-Tsang; Ho, Thi Hang; Nguyen, Bao Trung; Lin, Yu-Lin; Chiu, Po-Yu
Abstract: The Nile tilapia ( Oreochromis niloticus ) is one of the major food fish species produced in tropical and subtropical regions. However, this industry has been facing significant challenges from microbial infections. Understanding how hosts initiate immune responses against invading microbes is the first requirement for addressing disease outbreak prevention and disease resistance. Toll-like receptors (TLRs) are a family of evolutionarily conserved proteins that can recognize pathogen-associated molecular patterns (PAMPs). They thus play an essential role in innate immunity. TLR25 is a newly identified fish-specific member of the TLR1 subfamily. In this study, we investigate the molecular and functional characteristics of O. niloticus TLR25 ( OnTLR25 ) via tissue expression patterns, gene expression modulation after challenge with bacteria and TLR ligands, subcellular localization in human and fish cells, and the signaling pathways TLR25 may induce. Transcriptional levels of OnTLR25 are high in immune-related organs such as the spleen and head kidney, and are increased following bacterial challenges. In addition, we show that OnTLR25 preferentially localizes to the intracellular compartment in transfected tilapia head kidney (THK) cell line. Furthermore, overexpression of the truncated form of OnTLR25 in THK cell line induced the expression of proinflammatory cytokines, such as tumor necrosis factor α, interleukin ( IL ) -1β, IL-8, IL-12a, and interferon-d2.13 . Combined, our results suggest that TLR25 is likely to play an important role in the antimicrobial responses of the innate immune system of Nile tilapia. Highlights: OnTLR25 is expressed at higher levels in immune-related organs. OnTLR25 expression levels were significantly elevated by LPS, LTA, and zymosan. Bacterial infection induced OnTLR25 transcription. OnTLR25 preferentially localizes to the intracellular compartment. Overexpression of truncated OnTLR25 activates immune-related signaling pathways.